Two Women Writers and Their Italian Tours : Mary Shelley's Rambles in Germany and Italy 1840, 1842 and 1843 and Lucja Rautenstrauchowa's In and Beyond the Alps. - Ozarska, Magdalena (The Edwin Mellen Press, 2014)
A critical analysis of the form of the Romantic travelogue, making use of material that comes from two women writers from two different parts of Europe, but refers to the same subject matter- i.e. mid-19th century travels in Italy.